2020
DOI: 10.1126/sciadv.abc3699
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid (101955) Bennu’s weak boulders and thermally anomalous equator

Abstract: Thermal inertia and surface roughness are proxies for the physical characteristics of planetary surfaces. Global maps of these two properties distinguish the boulder population on near-Earth asteroid (NEA) (101955) Bennu into two types that differ in strength, and both have lower thermal inertia than expected for boulders and meteorites. Neither has strongly temperature-dependent thermal properties. The weaker boulder type probably would not survive atmospheric entry and thus may not be represented in the mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
161
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 102 publications
(178 citation statements)
references
References 95 publications
17
161
0
Order By: Relevance
“…This interpretation is consistent with results from thermal analysis presented by Rozitis et al. (2020), showing that an areal dust layer <50 µm thick covering 5–10% of the surface could be consistent with their observations. In addition, Hamilton et al.…”
Section: Discussionsupporting
confidence: 93%
“…This interpretation is consistent with results from thermal analysis presented by Rozitis et al. (2020), showing that an areal dust layer <50 µm thick covering 5–10% of the surface could be consistent with their observations. In addition, Hamilton et al.…”
Section: Discussionsupporting
confidence: 93%
“…Considering that the surface of Bennu is dominated by boulders with little apparent fine-grained regolith (Lauretta et al 2019;DellaGiustina et al 2019), these small particle sizes suggest a coating of fine particulates on top of the boulder surface, supporting other findings from OSIRIS-REx data: Independent analyses of OTES observations (Hamilton et al 2020) suggest that the spectral differences observed over Bennu's global surface could be attributable to the presence of a thin layer of fine particulates (<65-100 µm). The sizes retrieved by their models are consistent with thermal inertia results that limit any dust coating on Bennu's boulder-covered surface to <50 µm (Rozitis et al 2020a).…”
Section: Resultssupporting
confidence: 80%
“…In early observations of Bennu, DellaGiustina and Emery et al [24] found evidence of a multimodal particle population having distinct normal albedo ranges and PSFDs. Recent work has confirmed the presence of at least two distinct particle populations on the basis of spectral, geomorphologic [58], and thermal [62] analyses: (i) a high-reflectance, high-thermal-inertia population of smooth, angular particles, all of which are smaller than~20 m, and (ii) a more common low-reflectance, low-thermal-inertia population of rough, hummocky particles that spans the full-size range of measured objects (up to~100 m). Both are present within the candidate sample sites (Figure 11) [63] suggesting that Bennu's heterogeneity [58] extends to small scales (<1 m).…”
Section: Properties Of Bennu Discernable From the Psfdsmentioning
confidence: 95%